Rumination and Cognitive Distraction in Major Depressive Disorder: An Examination of Respiratory Sinus Arrhythmia - LeMoult, Joelle (J Psychopathol Behav Assess, 2015)
Difficulty regulating emotions following stressful events is a hallmark of Major Depressive Disorder (MDD). Although individuals’ ability to regulate their emotions is believed to have direct consequences for both emotional and physical wellbeing, few studies have examined the cardiovascular effects of different emotion regulation strategies in MDD. To the best of our knowledge, the current study is the first to examine the effects of two emotion regulation strategies, cognitive distraction and rumination, on both self-reported sadness and respiratory sinus arrhythmia (RSA) in individuals with MDD and healthy controls (CTLs). Following a forced-failure stressor, participants were randomly assigned to a rumination or cognitive distraction condition. As expected, rumination increased sadness and triggered RSA withdrawal for both MDDs and CTLs. Interestingly, although cognitive distraction reduced sadness, it also triggered RSA withdrawal. Moreover, cognitive distraction was associated with greater RSA withdrawal for MDDs than CTLs. Thus, although depressed individuals are able to use cognitive distraction to emotionally recover from stress, it may be associated with greater cognitive effort. Adding low-cost physiological measures such as RSA into assessments has the potential to offer new and important information about the effects of emotion regulation on mental and physiological health.